2011
DOI: 10.1016/j.ajog.2011.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal betamethasone exposure has sex specific effects in reversal learning and attention in juvenile baboons

Abstract: Objective-We investigated effects of three weekly courses of fetal betamethasone (βM) exposure on motivation and cognition in juvenile baboon offspring utilizing the Cambridge Neuropsychological Test Automated Battery.Study design-Pregnant baboons (Papio sp.) received two injections of saline control (C) or 175 μg/kg βM 24h apart at 0.6, 0.65 and 0.7 gestation. Offspring [Female (FC), n = 7 and Male (MC), n = 6; Female (FβM), n = 7 and Male (MβM), n = 5] were studied at 2.6-3.2 years with a progressive ratio t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 88 publications
1
30
0
Order By: Relevance
“…The gender-specific outcomes show a striking parallel to sex specific effects in reversal learning in juvenile baboons following late second-early third trimester administration of betamethasone, a synthetic glucocorticoid (Rodriguez et al, 2011), in which males tended to show reductions in errors while females showed enhanced error levels, effects the authors attribute to altered programming. Moreover, these sex-specific changes were also highly discrimination problem specific.…”
Section: Discussionmentioning
confidence: 82%
“…The gender-specific outcomes show a striking parallel to sex specific effects in reversal learning in juvenile baboons following late second-early third trimester administration of betamethasone, a synthetic glucocorticoid (Rodriguez et al, 2011), in which males tended to show reductions in errors while females showed enhanced error levels, effects the authors attribute to altered programming. Moreover, these sex-specific changes were also highly discrimination problem specific.…”
Section: Discussionmentioning
confidence: 82%
“…Animal models Male-specific outcomes Langley-Evans et al (1996) Low-protein diet gives elevated blood pressure in male offspring relative to females Rat Kwong et al (2000) Low-protein diet increases blood pressure in male offspring Rat Ozaki et al (2001) Nutrient restriction (30% reduction) increases blood pressure and vascular dysfunction more in male offspring Rat Dodic et al (2002) Dexamethasone exposure gives increased blood pressure more in male offspring Sheep Franco Mdo et al (2002) Nutrient restriction (50%) reduces eNOS expression in aorta of male offspring Rat Alexander (2003) Reduced uterine perfusion causes sustained increase in blood pressure in male offspring Rat Ortiz et al (2003) Antenatal dexamethasone injection persistently elevates blood pressure in male offspring Rat Hemmings et al (2005) Hypoxia Lee & Rivier (1996) Ethanol exposure leads to exaggerated HPA stress response in young female offspring Rat Khan et al (2003) High-fat diet increases blood pressure in female offspring Rat Wilcoxon et al (2003) Ethanol exposure leads to decreased placental 11b-hydroxysteroid dehydrogenase-2 levels and left ventricular hypertrophy in female offspring High-fat diet leads to DNA hypomethylation in female placenta only Mouse Rodriguez et al (2011) Betamethasone exposure reduces associative learning more in female offspring Baboon Vickers et al (2011) Fructose exposure gives decreased placental weight, increased plasma leptin and glucose in female offspring Rat Epidemiology Male-specific outcomes Zaren et al (2000) Maternal smoking decreases birth weight and head circumference proportionally more in male offspring Human Goldenberg et al (2006) Placentas from preterm deliveries showed more lymphohistiocytic infiltration in male offspring Human Haley et al (2006) Prenatal exposure to alcohol increases the heart rate of female infant offspring more than males, but with the males showing a greater increase in plasma cortisol Human Mingrone et al (2008) Male offspring of obese mothers have higher levels of insulin secretion in response to GTT Human Female-specific outcomes Roseboom et al (2001) Higher rates of obesity in female offspring conceived during famine Human Clifton (2005) Maternal asthma in pregnancy causes altered placental glucocorticoid metabolism and growth in female offspring Human Stark et al (2009) Antenatal betamethasone administration increased placental 11b-hydroxysteroid dehydrogenase-2 activity in female offspring and this was positively correlated with mean arterial blood pressure…”
Section: Main Results Speciesmentioning
confidence: 99%
“…54,55 There is also abundant evidence of excess levels of glucocorticoids in utero impairing brain development and later behavior in humans and animal models [56][57][58][59][60][61][62][63][64][65][66][67] including baboons. 68 Although we did not assess postnatal androgen or glucocorticoid levels in offspring, this should not preclude conclusions based on gestational exposure affecting behavioral performance. Evidence does exist of elevated androgens in male rats small for gestational age.…”
Section: Discussionmentioning
confidence: 99%